Length–weight relationships of six fish species from the headstream region of the Dongjiang River, China. (2nd November 2017) - Lin, F.; Zhou, Q. H.; Yang, D. H.; Lu, Z. L.; Zhang, J.
Summary: Dongjiang River, a main tributary of the Pearl River, is geographically situated in South China. The present study describes the length–weight relationships (LWRs) of six fish species ( Acrossocheilus paradoxus, Barbodes semifasciolatus, Onychostoma elongatum, Microphysogobio fukiensis, Microphysogobio kiatingensis, Metzia lineata ) from the headstream region of the river including five Chinese endemic species ( A. paradoxus, B. semifasciolatu, O. elongatum, Mi. fukiensis, Mi. kiatingensis ). Fish species of five genera of the same family were collected quarterly from April 2012 to October 2014 by using non‐selective fishing gears: drag nets (5 m, mesh‐size 3 cm), drift gillnets (30 × 15 m, mesh‐size 5 mm), fish cages (4 m, mouth opening 40 × 40 cm), scoop nets (mesh‐size 0.5‐1 cm), and electro‐fishing (12V, 200 Hz). The parameter a and b in the LWR equations ( W = a L b ) ranged from 0.0014 to 0.0228, and 2.89 to 3.18, respectively. Compared with FishBase, this study provides the first LWR records for four cyprinids ( A. paradoxus, B. semifasciolatu, O. elongatum, Me. lineata ) and a new record of maximum body length for O. elongatum .